Tryb postępowania przed organem rentowym w sprawach świadczeń z tytułu wypadku przy pracy - Wojciechowicz, Joanna (Studia Prawa Publicznego, 2019)
This article discusses the practical aspects of recognizing an occurrence as a work-related injury. The Act of 30 October 2002 on Social Insurance against Work-related Injuries and Occupational Diseases (consolidated text of 2018, item 1376) contains only a general definition of a ‘work-related injury.’ Moreover, it does not specify the meaning of the terms which are used in it, particularly of terms such as a ‘sudden occurrence’ or an ‘external cause.’ Many problems stem from a lack of criteria which should be used while deciding whether a ‘considerable contribution to the injury’ due to being under the influence of alcohol or drugs as defined in Article 21 of the Act has occurred. Therefore, during a preliminary investigation, a disability pension authority must determine whether the occurrence in question is a work-related injury. To that end it investigates whether the insured person has contributed to this occurrence to a considerable degree because if he has, such a conduct excludes the right to a work injury benefit. Accordingly, employees of the Social Insurance Company examine the accident scene and collect information in the workplace, from the prosecutor’s office, the police, or the healthcare centre, or by interviewing witnesses. Having documented the factual circumstances and explained all the existing doubts they are then able to define the terms and draw correct conclusions which result in a decision to award a benefit or to refuse it. Owing to the fact that the regulations concerning issues of recognizing an occurrence as a work-related injury and rights to a benefit are general clauses, it is necessary to be familiar with the current case-law. Without following the trends in the case-law of the Supreme Court one is not able to interpret facts and occurrences properly and hence the assessment of whether the insured is entitled to a work injury benefit is not possible.